Perceived birth trauma in Macedonian women - Pop-Jordanova, Nada; Maretti-Jakovska, Tatjana; Zorchec, Tatjana (Macedonian Academy of Sciences and Arts, 2023)
Although the childbearing is perceived as pretty normal and happy event, new research showed that the psychological birth trauma is however a universal and not rare phenomenon. Traumatic birth experiences can cause postnatal mental health disturbance, fear of childbirth in subsequent pregnancies and disruption to mother-infant bonding, leading to impaired child development. The purpose of this research was to evaluate collected data from several obstetric clinics as well as for primary paediatric settings related to 'Birth Trauma' in order to review especially women with symptoms of PTSD following childbirth. The study is prospective, starting from 2021 and ended in December 2022. The psychological instrument used in this research delivered named Intersect Questionnaire. The questionnaire is composed of 59 questions grouped in VIII parts. The presented results from our study confirmed that the birth trauma is not rare phenomena in our country, as well. Symptoms correlated with PTSD were present as follows: unpleasant memories (2,7%), anxiety (38,54%), panic (6,47%), traying not remember delivery (4,04%), self-accusation (2,16%), negative emotions (1,89%), alienation (4,31%), irritation/aggression (1,89%), self-destruction (1,89%), impulsiveness (4,31%), problems with concentration (3,23%), and sleeping problems (21,88%). These results alarm for better understanding this vulnerable period of women’s life. As a general conclusion we must highlight the importance of birth trauma in women, phenomena which is conformed worldwide and which be overcome as quickly and successfully as possible.
Keywords: birth trauma; midwifes; PTSD; babies